An analysis of existential feminism on Bombshell (2019) movie - Niken Ayu Lestari; Diana Aggraeni; Tri Arie Bowo (Jurnal CULTURE (Culture, Language, and Literature Review), 2023)
Feminism existentialists focus on women's existence as an object for men. This study analyzes existential feminism in Bombshell movie, released in 2019, written by Charles Randolph and directed by Jay Roach. This study used existentialist feminism by Simone de Beauvoir. The study aims to discover how women exist as "the other" and how the resistance form of women exists in Bombshell's 2019 movie. The research method used in this study is a descriptive-qualitative method to analyze the data. The result of the study found about 3 (three) women's existence as "the other," which consists of (1) The different positions of women and men, (2) Violence against women, (3) Sexual harassment, and also found about 4 (four) the resistance form of women existence, which consists (1) Women can work, (2) Women can become intellectuals, (3) Women can work as socialist transformation for society, (4) Surpass their limit, and the study showed if there still discrimination forms towards women that had been happened with women characters on Bombshell 2019 movie. Also, there were the resistance forms of women characters in Bombshell 2019 movie to resist their existence as "the other."